“Nuevas orientaciones dogmáticas, procedimentales Ley 30057: impacto en el ordenamiento jurídico administrativo sancionador disciplinario peruano” - Osorio Montoya, Pedro Alejandro (2019)
ABSTRAC The present investigation, doctrinal - normative, is directed to analyze, from the legal - administrative Peruvian sanctioning reality, the new orientations that the Sanctioning Power of the Public Administration in Peru has assumed, that has gone from a dual conception: ( corrective-disciplinary) to one of plural nature: (Corrective, Disciplinary, Ethical and Functional Administrative Responsibility) and each, have their own Law, Principles, Unlawful, Sanctions and Procedures, as will be explained in the development of this Thesis, influencing the nature of the Disciplinary Sanctioning Administrative Power. The doctrinal innovations - procedural required, is an effort to optimize, promote transparency and speed in public management, without undermining the rights of workers when they exercise the public function, which legally assume a new condition: by their relationship Statutory civil servant: High Officials of the State (it is not matter of study of this thesis), Officials and employees; and in this research process has been used the inductive - deductive, analytical - synthetic and hermeneutic - legal methods, which has led us to specify the impact that Law No. 30057: Civil Service, has in the legal - administrative disciplinary sanction in Peru.